'My Soul Is Changed': Pirate Identity and Shifting Power in Byron's Corsair. Issue 1 (June 2016) - Harris, Kirsty J.
Abstract : This essay explores power relations between two protagonists in Byron's 1814 poem The Corsair, arguing that the central figure Conrad fails as both hero and piratical subject. Conrad's inability to embrace change and discard his gentrified history and land-based lifestyle makes him a weaker character than the harem queen Gulnare. I argue that Gulnare takes the role of heroine by becoming a piratical aggressor, embracing and encouraging the adaptations required of her during the narrative. By analysing Conrad's lack of fluidity as opposed to Gulnare's ability to adapt to change, I argue that change is essential for survival in the piratical world of the poem. In order to break boundaries in the world of The Corsair, characters must be first prepared to reform their own identities or be responsible for their own destruction. By the end of the poem it is Gulnare, rather than Conrad, who has earned the designation Corsair.